Molecular Identification of Two Rare Actinomycetes Isolated from Mosul, Iraq - Talal Sabhan Salih (Indonesian Journal of Biology Education, 2020)
Rare actinomycetes from diverse habitats are continued to be isolated and screened for their novel bioactive compounds. The present study aims to molecular, morphological and physiological characterisation of two rare actinomycetes isolated from an Iraqi soil. Based on the 16S rRNA gene sequencing, the two isolates were categorized into two different rare genera Actinoplanes and Amycolatopsis that were designated as Actinoplanes sp. MOSUL and Amycolatopsis sp. MOSUL respectively. Phylogenetic trees analyses revealed that Act. sp. MOSUL was closely related strain to Act. xinjiangensis (jgi.1107663; identity 96.75%) and Act. lobatus (AB037006; identity 96.76%), and Amy. sp. MOSUL was most related to Amy. bullii (HQ65173099; identity 99.71%) and Amy.  tolypomycina (FNSO01000004; identity 99.26%). The two rare isolates had different morphological properties when grown on International Streptomyces Project (ISP) media, and different physiological and biochemical patterns when grown on Minimal Medium (MM) agar alone or supplemented with different carbon or chemical sources. The ribosomal 16S gene sequences of both Act. sp. MOSUL and Amy. sp. MOSUL strains were submitted to the National Center for Biotechnology Information (NCBI) and deposited in the GenBank database under the accession numbers MN095717 and MN095769 respectively.